STRUCTURAL CONSTRUCTIVE SOCIETY IN SIDNEY SHELDON’S THE STARS SHINE DOWN - Gunawan, Natacya Sheryl; Sari, Dian Eka (LINGUA LITERA : journal of english linguistics and literature, 2024)
This research aims to explain ways to construct a structural constructive society and severalfactors to establish it in The Stars Shine Down written by Sidney Sheldon in 1992. It uses adescriptive qualitative method. The Constructive Structuralism theory by Pierre Bourdieu isused by applying four concepts: capital, fields, structure, and strategy. This research revealsthat leaders have the right to control and manage their society. Also, the holding capital canforce the lower class to obey their order. The existence of ruler depends on the amount oftheir capital and the way they compete to defend their position in society.